God is green : an eco-spirituality of incarnate compassion - Shore-Goss, Robert (Eugene, Oregon : Cascade Books, 2016)
At this time of climate crisis, here is a practical Christian ecospirituality. It emerges from the pastoral and theological experience of Reverend Robert Shore-Goss, who worked with his congregation by making the earth a member of the church, by greening worship, and by helping the church building and operations attain a carbon neutral footprint. Shore-Goss explores an ecospirituality grounded in incarnational compassion. Practicing incarnational compassion means following the lived praxis of Jesus and the commission of the risen Christ as Gardener. Jesus becomes the "green face of God" Restrictive Christian spiritualities that exclude the earth as an original blessing of God must expand. This expansion leads to the realization that the incarnation of Christ has deep roots in the earth and the fleshly or biological tissue of life. This book aims to foster ecological conversation in churches and outlines the following practices for congregations: meditating on nature, inviting sermons on green topics, covenanting with the earth, and retrieving the natural elements of the sacraments. These practices help us recover ourselves as fleshly members of the earth and the network of life. If we fall in love with God's creation, says Shore-Goss, we will fight against climate change.
Includes bibliographical references.
Description based on print version record.
Keywords: Ecotheology; Ecology -- Religious aspects -- Christianity; Spirituality; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books